Sistem Pemberian Tarif Bagi Pendakwah Menurut Perspektif Hukum Islam Dan Konvensional - Muhammad Muttaqin; Muhibban Muhibban; Muhammad Misbakul Munir; Nurul Amalia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to evaluate the legal aspects of both Islamic and conventional laws regarding the remuneration provided to preachers invited by Masjid Raya Aziziyah Secanggang. Preachers play a crucial role in guiding individuals towards goodness and deterring them from evil, as per the teachings of the Quran. The study has two primary objectives: to examine the remuneration system for preachers in the mosque and to analyze the perspectives of Islamic and conventional laws on this system. The research methodology employed is qualitative-descriptive with a field approach, utilizing interviews, observations, and documentation as data sources. The findings indicate that Masjid Raya Aziziyah Secanggang compensates preachers through two methods: direct payment without a formal agreement and through a written agreement. From an Islamic legal standpoint, remuneration for preachers can be considered a permissible (mubah) form of appreciation or gratitude. In terms of conventional law, the remuneration system aligns with the regulations outlined in the 2023 Job Creation Law. This research underscores the importance of maintaining compliance with both Islamic and conventional legal aspects and ensuring collective benefits to uphold a fair and justified remuneration system for preachers at Masjid Raya Aziziyah Secanggang. Mutual respect for rights and responsibilities is crucial to enhancing the quality of this remuneration system.